Kajian potensi pariwisata Pulau Bidadari melalui pendekatan ekowisata - ABDULLAH, M. Reza ([Yogyakarta] : Universitas Gadjah Mada, 2009)
The present research, basically, has five objectives, namely: to (1) obtain the clarity of physical and non physical potentials that the Bidadari Island has to support the development of tourism sector in the Seribu Islands; (2) identify the perception of tourists on tourism products in the Bidadari Island able to be used in developing ecotourism-based tourism activities in Bidadari Island; (3) obtain factors can be used in developing the Bidadari Island as a tourism destination; (4) obtain the development accessibility model suitable implemented in the Bidadari Island; (5) obtain recommendation can be used to develop Bidadari Island tourism as one of leading tourism destinations in Indonesia. To achieve aforementioned objectives, research methods used involved the combination of qualitative and quantitative analyses. Qualitative analysis was conducted through observations and interviews with the Bidadari Island management, government and community as tourism business actors. Quantitative analysis was carried out using questionnaires distributed among tourists in the Bidadari Island. Results indicate that: (1) Bidadari Island has various potentials of tourism attraction consisting of natural and cultural tourisms. (2) Profile of tourists shows that most of the tourists coming from Jakarta with ages ranging of 25-40 years, university graduates and having established employment. Tourists tend to visit the Bidadari Island in groups (institutions/ companies) under motivation of being relax or escaping from daily work routines. Activities they frequently perform involve observing flora and fauna where monitor lizard and elang bondol (bondol hawks) have been “points of interest” fascinating tourists. (3) Tourists’ perception on tourism products in Bidadari Island state that several important factors should be the main attention for the management in improving the quality product of Bidadari Island tourism as the following: Types and variety of attractions; Reliable ticket and accommodation prices offered; the Quality of transportation modes; the frequency of transportation modes; Food and Beverage facilities; Shopping and souvenirs facilities. (4)Accessibility models appropriate to be developed in Bidadari Island consisted of two, i.e. external and internal accessibility. Based on the results, it is concluded that eco-tourism concept holds the principles of nature based, ecologically sustainable, generating visitor satisfaction, environmentally educative, and locally beneficial as highly appropriate to be used in Bidadari Island tourism development.